(untitled) (Research, Society and Development, 2023)
This work aimed to evaluate the biological degradation and natural durability of forest species from the Amazon in a decay field in Acre. The work was carried out in the experimental field of Embrapa Acre between 2015 and 2022. The stakes measuring 0.05 x 0.05 x 0.50 meters were randomly distributed and buried in the rotting field at 0.25 m deep in. Field evaluations were carried out quarterly, registering the incidence of xylophagous fungi and termites and the damage caused to cuttings of 36 forest species. The species of fungi and termites were collected and maintained at Embrapa Acre’s Phytopathology and Entomology Laboratories and identified in several specialized laboratories in Brazil. The degradation of the piles was carried out assigning scores from zero to four according to the varying percentage of degradation. The wood staining fungi identified in this research were: Aspergillus, Fusarium, Penicillium, Trichoderma, Nigospora, Lasodiploidia, Cladosporium and Curvullaria. The wood rotting fungi that occurred in the cuttings were: Gloeophyllum striatum, Hexagonia hidinoide, Datronia scutellata, Tramets and Picnoporus. Eleven species of termites were identified; The main termite species T teneus was responsible for 91.6% of occurrences. The species most attacked by H. tenuis was the pink cedar (Cedrela odorata) and the least attacked was the angelim-da-mata. The canelão, freijó and yellow imbiridiba species were not infested by termites. The wood species that had the highest rate of degradation were the hard mulungu, Blond Itaúba, mulateiro, Black Marupá.